How Imaging Glutamate, γ‐Aminobutyric Acid, and Dopamine Can Inform the Clinical Treatment of Alcohol Dependence and Withdrawal. (28th October 2015) - Hillmer, Ansel T.; Mason, Graeme F.; Fucito, Lisa M.; O'Malley, Stephanie S.; Cosgrove, Kelly P.
Abstract : Neuroimaging studies have dramatically advanced our understanding of the neurochemical basis of alcohol dependence, a major public health issue. In this paper, we review the research generated from neurochemical specific imaging modalities including magnetic resonance spectroscopy, positron emission tomography, and single‐photon emission computed tomography in studies of alcohol dependence and withdrawal. We focus on studies interrogating γ ‐aminobutyric acid (GABA), glutamate, and dopamine, as these are prominent neurotransmitter systems implicated in alcohol dependence. Highlighted findings include diminished dopaminergic functioning and modulation of the GABA system by tobacco smoking during alcohol withdrawal. Then, we consider how these findings impact the clinical treatment of alcohol dependence and discuss directions for future experiments to address existing gaps in the literature, for example, sex differences and smoking comorbidity. These and other considerations provide opportunities to build upon the current neurochemistry imaging literature of alcohol dependence and withdrawal, which may usher in improved therapeutic and relapse prevention strategies. Abstract : Neuroimaging targets specific to the GABA, glutamate, and dopamine systems in alcohol dependence. Dashed yellow lines indicate neurotransmitter concentrations measured with magnetic resonance spectroscopy (MRS). Specific targets highlighted in yellow denote targets imaged with positron emission tomography (PET) or single‐photon computed emission tomography (SPECT).